Price Promotion Elasticity and Profitability : Case Study of Hair Care and Coloration Market in the Czech Republic - Ponomarenko, Andrii; Karlíček, Miroslav, 1979-; Furman, Marko; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
This thesis examines differences in price promotion elasticity and profitability and the drivers for these differences in the context of a multinational company operating in the hair care and coloration market in the Czech Republic. Two research objectives are pursued in the thesis: the first objective is to identify what brand and category characteristics drive price promotion elasticity and profitability; the second research goal is to evaluate the profitability of price promotions for a selected manufacturer. To achieve the objectives, 642 weekly observations were analyzed in the study of price promotion elasticity and 231 observations in the analysis of price promotion profitability. Analysis of variance (ANOVA) was performed to identify the effects of the independent variables on promotion elasticity and profitability. The thesis identified that brands with higher levels of market share, brand equity, manufacturer’s media advertising, in-store promotional support, and event association experience higher price promotion elasticity. Conversely, a number of brands in the product category is negatively associated with price promotion elasticity. With regards to the profitability, high-share brands appeared to enjoy more profitable price promotions whereas the promotion profitability of the premium-priced brands is not significantly different from those of low-equity. In addition, high levels of media advertising and in-store promotional support are negatively associated with price promotion profitability. Finally, a higher number of brands in the product category and the event association has a negative effect on the promotion profitability. The thesis concludes by indicating the ways for the manufacturer to improve the effectiveness of price promotions and suggesting the limitations and direction for further research.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses